EFFECT OF FUNCTIONAL COMPETENCE AMONG ELDERLY - A, GAYATHRI; N, RAJANI (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
India is aging with 8.5 per cent of the population being elderly; the study of elderly is of immense social relevance. Aging without tears being the goal of Gerontology and “Long life” being the aspiration of one and all, the investigation of characteristics of long evous persons is of direct significance. Knowledge of characteristics of the old-old can lead to appropriate interventions that will promote a “Livelier Longevity”. For the present study the subjects would consist of 60 men and women in the age groups of 80-89 (old). Results showed that Livelier Longevity is related to functional competence is determined by certain markers viz., physical and mental activities, social supports, health practices, age, gender and economic status. Findings highlight the need for creating need based support services for the vulnerable elderly in the Indian context.